"Preñada estaba la encina": de los nuevos nacimientos simbólicos sin madre a la inesperada armonía paterno-filial en "Los trabajos de Persiles y Sigismunda" - García González, Sylma (El Colegio de México, 2013)
This article centers on the analysis of the configuration and developmentof the paternal and maternal characters in Los trabajos de Persilesy Sigismunda, a novel written by Spanish author Miguel de Cervantes.These characters are anything but one-dimensional and while being aclear representation of the social and religious views of the time --particularlythe honor code--, some of the paternal Cervantine characterspossess certain traits that make them unique within the Spanish literatureof the Golden Age. They are complex characters; in fact, someeven face profound personality evolutions.